2017
DOI: 10.1080/09542299.2017.1356694
|View full text |Cite
|
Sign up to set email alerts
|

Scavenging Rhodamine B dye usingmoringa oleiferaseed pod

Abstract: Moringa oliferia seed pod was modified using orthophosphoric acid (H 3 PO 4 ) and used as adsorbent for sequestering Rhodamine B (Rh-B) dye from aqueous solution. The acid-modified adsorbent (MOSPAC) was characterized using Scanning Electron microscopy (SEM), Fourier Transform Infra Red (FTIR), Energy Dispersive X-ray (EDX), pH point of zero charge (pH pzc ) and Boehm Titration (BT) techniques, respectively. Operational parameters such as contact time, initial dye concentration, adsorbent dosage, pH and soluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
65
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 65 publications
(72 citation statements)
references
References 77 publications
6
65
0
Order By: Relevance
“…3. Similar result was obtained by Bello et al, (2017). The difference in the adsorption capacity as the pH increases may be due to the formation of different ionic species and surface charges.…”
Section: Effect Of Phsupporting
confidence: 84%
“…3. Similar result was obtained by Bello et al, (2017). The difference in the adsorption capacity as the pH increases may be due to the formation of different ionic species and surface charges.…”
Section: Effect Of Phsupporting
confidence: 84%
“…There was relatively constant dye uptake at 25 min of the contact time, that is, 105-120 min. Our previous study has shown that the adsorption tends to be rapid in the first 10-15 min and steadily reduces until equilibrium is attained (Bello et al 2017b). The reason for this was due to the large number of free pores on the surface of the activated coconut husk which enhanced the rapid uptake of Rh-B dye at the initial stage.…”
Section: Effects Of Contact Time and Initial Dye Concentrationmentioning
confidence: 97%
“…4, the pH pzc was determined to be at 3.69. This implies that adsorption of cations was improved at pH values higher than pH PZC , while anions adsorption is favored at pH value less than pH PZC (Farahani et al 2011;Bello et al 2017b;Olakunle et al 2018). It can be deduced from Fig.…”
Section: The Ph Point Of Zero Charge (Ph Pzc ) Determinationmentioning
confidence: 99%
See 2 more Smart Citations